RITUAL MONIBI SEBAGAI PERFORMATIF REALITAS SOSIAL DALAM MENJAGA STABILITAS DESA SINIYUNG KECAMATAN DUMOGA BOLAANG MONGONDOW - Inkiriwang, Rivo Ronaldo Rivo; Tampake, Tony (Paradigma: Jurnal Kajian Budaya, 2025)
This article aims to explore the practice of Monibi cultural rituals in Siniyung Village, Dumoga Bolaang Mongondow District. The focus of research on Monibi culture is rarely carried out in Bolaang Mongondow. The fact that the only one, that still practices Monibi culture in Bolaang Mongondow is Siniyung Village. The author uses literature review with the aim of exploring the cultural values of Monibi ritual practice in Siniyung Village, and is equipped with interview collection techniques to support the validity of fdata. The Monibi Ritual is studied in the perspective of David Salomon, Monibi ritual as a performative act of social reality in maintaining social stability. Monibi is a space for individuals to understand themselves as part of a group and reveal the meaning of time along the journey of life of the people in Siniyung Village. This research has found that the practice of the Monibi ritual aims to reject reinforcements, begging for forgiveness, ask for sustenance, and grateful to God (Ompu Duata). Laudation and Sacrifice in the ritual process are meaningful as a form of intense communication between the community and the presence of Ompu Dua ta and their forefather. Eating together is a symbol of collective solidarity and ritual of Monibi as an existence for form of sacred meaning construction. In other words, the Monibi ritual becomes a performative of social reality in maintaining the stability of Siniyung Village, Dumoga District.